Sentiment Analysis of Comments on Instagram Account @Kalis Mardiasih Regarding Advocacy for the Nia Kurnia Sari Case: A Critical Feminist Approach - Khairani, Leylia (PERSPEKTIF, 2025)
This study explores public sentiment on Instagram regarding advocacy around the tragic case of Nia Kurnia Sari, a young street vendor brutally murdered in an act of gender-based violence. The case underscores urgent issues of gender inequality and societal responses to violence against women, providing a significant context for this research. Using a critical feminist lens, the study analyzes 251 comments from the Instagram account @KalisMardiasih, employing a mixed-methods approach that integrates quantitative sentiment analysis and qualitative thematic coding. Sentiment analysis, conducted through Python notebooks to automate data processing, reveals that 45% of comments express empathy and solidarity with the victim, while 35% exhibit victim-blaming and skepticism toward feminist advocacy. The remaining 20% are categorized as neutral, including ambivalent statements, requests for more information, or non-committal responses. This neutral category offers essential insights into audience engagement dynamics. Thematic analysis identifies key themes such as solidarity, demands for systemic reform, and resistance rooted in patriarchal norms. Instagram emerges as an empowering platform for feminist advocacy and a contested space where progressive and conservative ideologies collide. These findings emphasize the importance of sustained advocacy and education to combat gender-based violence and advance gender equality.